Australian radiation therapy - Part Two: Reflections of the past, the present, the future - Merchant, Susan; Halkett, Georgia; Sale, C. (Wiley, 2014)
INTRODUCTION: Documentation on the history of Australian radiotherapy is limited. This study provides radiation therapists' (RTs) perspectives of the people, workplace, and work practices in Australian radiotherapy centres from 1960 onwards. It provides a follow-up to our previous study: Australian radiation therapy: An overview – Part one, which outlines the history and development of radiotherapy from conception until present day. METHODS: Four focus groups were conducted on separate occasions in 2010, one in South Australia and three in Victoria, Australia. Participants who worked in radiotherapy were purposively selected to ensure a range of experience, age, and years of work. RESULTS: From a RT perspective, radiotherapy has evolved from a physically demanding ‘hands-on’ work environment, often with unpleasant sights and smells of disease, to a more technology-driven workplace. CONCLUSION: Understanding these changes and their subsequent effects on the role of Australian RTs will assist future directions in advanced role development.